Inflammatory Cytokines Interleukin-1β and Tumour Necrosis Factor-α - Novel Biomarkers for the Detection of Periodontal Diseases: a Literature Review - Maria Gerusa Brito Aragão; Francisco Cesar Barroso Barbosa; Mirna Marques Bezerra; Vicente de Paulo Teixeira Pinto; Hellíada Vasconcelos Chaves (Stilus Optimus, 2016)
Objectives: The article aims to discuss the IL-1β and TNF-α potential use as salivary biomarkers of periodontal diseases pathogenesis and progression. Material and Methods: This literature review has been registered in PROSPERO database with following number: CRD42016035729. Data investigation was performed on PubMed database as the main source of studies. The following search terms were used: "salivary biomarkers", "periodontal diseases", "TNF-alpha", "Interleukin-1 beta". Clinical trials and animal experimental models of periodontal disease were included in the discussion. In regards to inclusive dates, published studies from January 2006 to December 2015 were considered in this review along with the mentioned inclusion criteria. Results: IL-1β and TNF-α salivary levels increased in diseased groups, they were associated with onset and disease severity, and their levels reduced in response to periodontal therapy. IL-1β and TNF-α could be promising biomarkers in the detection of periodontal diseases. Conclusions: The use of a salivary cytokine-based diagnosis appears to be a screening method capable of diagnosing periodontal diseases in an early fashion, establishing an era of individualized clinical decisions.